Pengaruh Gawai Terhadap Perkembangan Komunikasi Sehari-Hari Anak Usia Dini - Sulistiyaningrum, Annisa; Purnama, Mardiyah; Fauziah, Siti; Zulkarnain, Ali Iskandar (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Daily life is undergoing significant changes due to the rapid development of information technology, such as early childhood interactions and parenting patterns. Children prefer to play conventional games and interact with others thru devices like computers, tablets, and smartphones. This study examines previous research on how device exposure affects communication and language development in young children. The qualitative literature review method analyzes various documents and scientific sources about the impact of devices. The results show that excessive gadget use hinders children's language and communication development because it reduces social interaction and direct verbal stimulation with parents and the surrounding environment. Children who use uncontrolled devices receive passive stimulation without two-way interaction, which is an important factor in developing verbal skills. The risk of speech delay and socio-emotional disorders increases due to a lack of interaction with peers and adults. However, using devices with educational encouragement and the active participation of parents and educators can enhance cognitive and language skills. Time management for devices, content monitoring, and access activation are important ways to help children develop optimally. For devices to become learning aids, the active role of parents and teachers is needed in guiding the use of technology. A balanced approach to digital and face-to-face learning in the Society 5.0 era enhances students' interest and communication skills. Additionally, teaching children healthy gadget usage is important. This can be achieved by limiting duration, choosing beneficial content, and maintaining a balance between the digital and physical worlds. To support children's overall communication and language development, the use of technology and direct social interaction must be balanced.